Field Survey on Usage of Non-Financial Measurement at Hotel in Japan - Mitani, Kayo (Journal of Advanced Research in Business and Management Studies, 2020)
This paper focuses on non-financial measurements related to customer and aims to clarify how customer-related measurements are affected in practice. The interviews are conducted to six domestic hotel companies and clarifies the actual situation to find problems for inhibiting the effective usage both of customer-related measurements and financial measurements. The results revealed that customer-related measurements are the helpful indicators for the decision-making involved in creating a future investment plan. On the other hand, it became apparent that there were some issues within the incentive system and personnel evaluation.